Health-Related Quality of Life After Pediatric Cochlear Implantation - Pereira, SA (2022)
Objectives: To examine the results of health-related quality of life (HRQoL) questionnaire scores from deaf children fitted with at least one cochlear implant (CI) and compare responses to normal-hearing age-peers (NHP) and to their parents. Methods: This cross-sectional study included 33 pediatric patients with a hearing experience of at least 1 year with CI and a control group of 21 NHP. The KINDLR questionnaire for measuring HRQoL (generic) in children (7-12years) and adolescents (13-17years) and a CI questionnaire (specific) were completed by CI users and their parents. Scores were transformed to a 100-point scale with 100 representing the most positive response. Results: The group of children and adolescents with CI reached a similar score in the generic HRQoL (Children:78,6; Adolescents:80,4; p = 0,35) and in the overall CI questionnaire (Children:77,6; Adolescents:75,6; p = 0,53). CI users in both age groups scored generic HRQoL similarly to their NHP (NH children:82,2, p = 0,18; NH adolescents:77,5; p = 0,07) and higher than CI users from other centers (OC) (OC children:75,4; OC adolescents:70,3). CI users scored their school domain lower than their NHP (p = 0,04). Generic and CI questionnaire scores of parents and their children correlated positively (r = 0,66, p = 0,00 and r = 0,73, p = 0,00). The total scores of HRQoL in the self-rating and parent rating correlate with none of the variables at study (gender, cause of deafness, age at implantation, years with a CI, chronological age) except with speech progression (p = 0,007). Conclusions: Children with CI experience similar quality of life as NHP. Parents are reliable reporters on the status of their child's overall quality of life.